Systems Biology Approaches and Precision Oral Health: A Circadian Clock Perspective - Adeola, Henry A.; Papagerakis, Silvana; Papagerakis, Petros (Frontiers in Physiology, 2019)
A vast majority of the pathophysiological/metabolic processes in humans are temporally controlled by a master circadian clock(CC) located centrally in the hypothalamic suprachiasmatic nucleus of the brain, and by specialized peripheral oscillators located in other body tissues. This CC system generates a rhythmical diurnal transcriptional-translational cycle in clock genes(CG) and protein expression and activities regulating numerous downstream target genes. CGs as key regulators of physiological function/dysfunction of the CC have been linked to various diseases and multiple morbidities. Emerging omics technologies permits largescale multi-dimensional investigations of the molecular landscape of a given disease and the comprehensive characterization of its underlying cellular components (e.g. proteins, genes, lipids, metabolites), their mechanism of actions, functional networks and regulatory systems. Ultimately, they can be used to better understand disease and interpatient heterogeneity, individual profile, identify personalized targetable key molecules and pathways, discover novel biomarkers and genetic alterations, which collectively can allow for a better patient stratification into clinically relevant subgroups to improve disease prediction and prevention, early diagnostic, clinical outcomes, therapeutic benefits, patient’s quality of life and survival. The use of ‘omics’ technologies has allowed for recent breakthroughs in several scientific domains, including the field of CC biology. Although studies have explored the role of clock genes using circadiOmics(which integrates circadian omics such as genomics, transcriptomics, proteomics and metabolomics) in human disease, no such studies have investigated the implications of circadian disruption in oral, head and neck pathologies(HNP) using multi-omics approaches and linking the omics data to patient-specific circadian profiles. There is a burgeoning body of evidence that CC controls development and homeostasis of oral and maxillofacial structures e.g. salivary glands, teeth and oral epithelium. Hence, in the current era of precision medicine, dentistry and patient-centred health care, it is becoming evident that a multi-omics approach is needed to improve our understanding of the role of CC-controlled key players in the regulation of HNP. This review discusses current knowledge on the role of the CC and the contribution of omics-based approaches towards a novel precision health era for diagnosing and treating HNP, with an emphasis on oral, head and neck cancer and Sjögren’s syndrome.